2019
DOI: 10.1248/cpb.c18-00926
|View full text |Cite
|
Sign up to set email alerts
|

Natural Inhibitors on Over-Activation of Microglia from Herbals

Abstract: Neuroinflammation manifested by over-activation of microglial cells plays an essential role in neurodegenerative diseases. Short-term activation of microglia can be beneficial, but chronically activated microglia can aggravate neuronal dysfunction possibly by secreting potentially cytotoxic substances such as tumor necrosis factor-alpha (TNF-α) and nitric oxide (NO), which can result in dysfunction and death of neurons. Therefore inhibiting over-activation of microglia and the production of cytotoxic intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Microglial inhibitors, including minocycline and natural products (e.g., apigenin, fisetin, and curcumin), show promise in the treatment of cognitive impairment associated with neuropsychiatric disorders, including schizophrenia 69 . Minocycline, a classical semi-synthetic tetracycline antibiotic with good brain infusion, is used most widely to inhibit microglial overactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Microglial inhibitors, including minocycline and natural products (e.g., apigenin, fisetin, and curcumin), show promise in the treatment of cognitive impairment associated with neuropsychiatric disorders, including schizophrenia 69 . Minocycline, a classical semi-synthetic tetracycline antibiotic with good brain infusion, is used most widely to inhibit microglial overactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, brain activity and multiple organ functions declined with aging [3]. Furthermore, cognitive deficiency and dementia related to brain elderly were identified as the directing sources of debility and dependency among worldwide elder people in the absence of effective therapeutic approaches [4]. 2.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Previous studies revealed that SE activated glial cells and intensified pro-inflammatory agents including TNF-α, and NO production, which are responsible for cell death and dysfunction in neuroinflammatory diseases. [18][19][20] Therefore, preventing the activation of TNF-α and NO pathways may control some neurological and peripheral effects.…”
mentioning
confidence: 99%